The ethical-political role of the Community Health Workers' job in a Vulnerable Territory: contributions of participatory research - Castro-Silva, Carlos Roberto; Abdala, Christiane Alves (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2023)
The consolidation of the Brazilian Unified Health System (SUS) principles requires innovative interventions and strategies, highlighting the proposal of the Family Health Strategy (FHS) as reorganizer of the health system. Although it is important to emphasize the mediation position occupied by Community Health Workers (CHW), such a position must be problematized considering the sociohistorical and cultural context in which these professionals work, especially when faced with the social determinations of health. The objective of this study was to reflect on the role of affectivity and ethical politics in the practices of the CHW. Based on participatory research, made feasible by a management group, participant observation recorded in field diaries and interviews, we point out aspects of intersubjectivity developed in the territory. According to the results, the potential for action of these professionals is related to the construction of spaces for welcoming and listening, which promote a critical and reflective awareness, capable of denaturing the suffering triggered by social exclusion. The main challenge is to value the friendship developed in the territory as a political exercise.